Manifestations of death and hope Sinan Antun’s “The Pomegranate Alone” is an example: A Semiotic study - Elsayed, Alaa; Alhashemi, Badeeah (Al-Adab Journal, 2025)
The semiotics of passions studies the feelings and emotions related to the human’s self within texts and narrative discourses. It also studies the negative and positive human emotions related to the body, in order to obtain the meaning and content by reading the structural and semantic components superficially and deeply, through analysis and interpretation.  By questioning the form of content, and determining the method or process by which meaning is constructed and shaped by drawing correspondences and differences.  This research aims to study the fictional text and monitor its erotic essence, and then identify its purposes and analyze them to move from the superficial structure to a more deeper one. It also reveals the procedural tools used in analyzing the desires semiotically, and analyzes the effect of their formation and the way they interact with the body.  This is done through analyzing the lexical manifestations, semantic fields, and the semiotic semiotic square, in addition to studying the passions using the erotic chart, which provides an analysis of the passions through five stages that include emotional exposure, preparation, the erotic axis, emotion, and moral evaluation.  The research concludes with results that reveal the passions controlling the erotic self in the novel, and the extent of their influence on the character’s emotions and their role in the novel.  It is represented by the desire for death, which is the main desire, and it is the primary driver of the events of the novel, as the characters react to the desire for death with acceptance, resistance, or fear.  In addition to the passion of hope, which was studied through its opposite, disappointment, to conclude the extent of its role in the compulsive self’s resistance to the surrounding circumstances.  Reaching the conclusion of the beginning of the formation of these passions and what they led to in their final form.